Attitudes of UP-CHE students towards virginity as a determinant in mate selection - Dizon, Jasmine Ison (UP College of Home Economics, 2012)
With the increase in acceptance of premarital sex, the value of virginity in mate selection is questioned. Whether or not it is still considered a determinant in choosing a life partner is explored in this study. This study aimed to identify, compare, and contrast the attitudes of UP CHE male and female students towards virginity. This study also aimed to identify the different factors that affected one's view on virginity. The researchers used two tools in gathering data: survey questionnaires for the quantitative part of the study and interviews for the qualitative part. Multi-stage sampling was used to obtain the respondents who fit the criteria specified in the study. They conducted surveys in classes that were offered to all courses such as HE 100 (Family Life and Societal Development), HE 101 (Ethics and Values in Family and Society) and CHE-CWTS 2 (Civic Welfare and Training Services). The researchers found that virginity in a relationship is more valued by females than males. They also found that there are various factors that affect a person's virginity. The respondents' views were highly influenced by their religion and family upbringing. Also, in choosing a mate, it was found that Love and Personality were the two criteria that both the male and female respondents valued most. Physical Attractiveness is the only point of difference between the two sexes in ranking the mate selection criteria, with males ranking it higher than the females did. Virginity is not considered of high importance and is seen as a bonus instead of a criterion on selecting one's life partner. Knowing the attitudes of a certain percentage of the Filipino youth towards virginity may help in gaining an better understanding of their sexuality and their attitude formation. As such, this research may be helpful for educators and parents when teaching values to the youth.